Beam Collimation during Lumbar Spine Radiography: A Retrospective Study - Karami V.; Zabihzadeh M. (Journal of Biomedical Physics and Engineering, 2017)
Introduction: Collimating the primary beam to the area of diagnostic interest (ADI) has been strongly recommended as an effective method to reduce patient’s radiation dose and to improve image quality during radiology practice. Lack or inadequate collimation results in excessive radiation dose to patients and deterioration image quality. Objective: To assess the quality of beam collimation during lumbar spine radiography at two general hospitals in Ahvaz, Iran. Materials and Methods: We retrospectively reviewed 830 digital anteroposterior (AP) lumbar spine radiographs in term of beam collimation. For each radiograph, the distance between current and optimal collimation was calculated (in cm). The area of ADI and total field size for each radiograph were also calculated (in cm2). Results: The total mean ADI and irradiated region outside ADI for each radiograph were estimated 360 and 454 cm2, respectively. The total irradiated region outside ADI was 1.26 times more than ADI. In contrast to cranial regions outside ADI, caudal regions were more commonly included inside the primary beam (12% vs. 24.4%; Pvalue <0.005). At least in 62% of radiographs evaluated, ovaries were included in the primary beam. Conclusion: Radiographers should make considerable effort to limit the primary beam to the ADI to reduce patient’s exposure and to increase image quality.